Pengaruh Penguasaan Al-Qawāʻid An-Naḥwiyyah Siswa Terhadap Kemampuan Qirāah pada Mata Pelajaran Bahasa Arab Kelas VIII MTs Ihsaniyah Banyumudal Moga Pemalang - Reni Wahyuni (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study aims to find out how much mastery of Al-Qawāʻid Al-Naḥwiyyah students have, how much Qirāah ability in Arabic subjects students have to find out whether there is a significant influence between students' mastery of Al-Qawāʻid Al-Naḥwiyyah on Qirāah ability in Arabic subjects class VIII MTs Ihsaniyah Banyumudal Moga Pemalang. This research is a field research using a quantitative approach. Data collection is carried out by the method of tests, observations, interviews and documentation. From the results of the research that has been carried out, it can be concluded that al-Qawāid Al-Naḥwiyah's mastery of Qirāah's ability in Arabic subjects of class VIII students in Arabic MTs Ihsaniyah Banyumudal Moga Pemalang subjects has a significant influence, this can be proven from the results of a simple linear regression analysis using the SPSS 26 program, which obtained a significance value (Sig.) of 0.000 which is less < than probability 0.05, and the calculated value is greater than the > of the ttabel value of 5,300 > 2,019, so a decision can be made that Ho is rejected and Ha is accepted.